Effect of mixed convection in MHD boundary layer flow over exponentially stretching sheet / Nur Farhana Mohamad Shauqi - Mohamad Shauqi, Nur Farhana (2023)
The study of boundary layer over an exponentially stretching sheet has gained importance in the engineering field over the year. The MHD boundary flow can be applied in various sector such as hydroelectric power plants, medicine and astrophysics. The addition of parameters such as magnetic parameter, thermal radiation parameter and mixed convection parameter has been proved to have significant effect on the momentum profile, temperature profile and concentration profile. This study considers the effect of mixed convection in MHD boundary layer flow over exponentially stretching sheet in double stratification. The governing partial differential equations are transformed into ordinary differential equations by applying the similarity substitution. The Runge-Kutta method with shooting technique in Maple software was used to solve the equations. The effect of mixed convection parameter, magnetic parameter, porosity parameter and Prandtl number are presented in graph and discussed. Based on the result obtained, it is found that the mixed convection caused the momentum boundary layer thickness to decrease. Meanwhile the thermal boundary layer thickness and concentration boundary layer increases with the increase of mixed convection parameter.